ECOLOGICAL DA’WAH STRATEGIES IN PROMOTING ENVIRONMENTAL CONSERVATION IN AMBON CITY - Hakis, Hakis; Masri, Abdul Rasyid; Tike, Arifuddin; Said, Nurhidayat Muhammad; Muliyadi, Irvan; Bin Kamarzaman, Mohd Haidar (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
The purpose of this research is to provide an alternative solution for ecological-based Daâ€™wah in the efforts to protect the environmental destruction in the city of Ambon. Ambon is a region surrounded by hills that are prone to disasters such as landslides and floods. Ecological-based daâ€™wah is considered an alternative solution to instill environmental values in the community for environmental conservation.This research is a qualitative descriptive type supported by quantitative data by using phenomenological approach. This research locates in the city of Ambon. Observation, interviews, questionnaires, documentation, and Delphi technique are used to collect the data related to the research questions. The data then are analyzed by using the following phases: Â data reduction, data presentation, interpretation, and drawing conclusions.The study identified at least five alternative solutions for ecological daâ€™wah in environmental conservation efforts in Ambon, namely: implementation of